Paeoniflorin Ameliorates Skeletal Muscle Atrophy in Chronic Kidney Disease via AMPK/SIRT1/PGC-1α-Mediated Oxidative Stress and Mitochondrial Dysfunction - Li, Qiang; Wu, Jing; Huang, Jiawen; Hu, Rong; You, Haiyan; Liu, Lingyu; Wang, Dongtao; Wei, Lianbo (Frontiers in Pharmacology, 2022)
Skeletal muscle atrophy is a common and serious complication of chronic kidney disease (CKD). Oxidative stress and mitochondrial dysfunction are involved in the pathogenesis of muscle atrophy. The aim of this study was to explore the effects and mechanisms of paeoniflorin on CKD skeletal muscle atrophy. We demonstrated that paeoniflorin significantly improved renal function, calcium/phosphorus disorders, nutrition index and skeletal muscle atrophy in the 5/6 nephrectomized model rats. Paeoniflorin ameliorated the expression of proteins associated with muscle atrophy and muscle differentiation, including muscle atrophy F-box (MAFbx/atrogin-1), muscle RING finger 1 (MuRF1), MyoD and myogenin (MyoG). In addition, paeoniflorin modulated redox homeostasis by increasing antioxidant activity and suppressing excessive accumulation of reactive oxygen species (ROS). Paeoniflorin alleviated mitochondrial dysfunction by increasing the activities of electron transport chain complexes and mitochondrial membrane potential. Furthermore, paeoniflorin also regulates mitochondrial dynamics. Importantly, paeoniflorin upregulated the expression of silent information regulator 1 (SIRT1), peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α) and phosphorylation of AMP-activated protein kinase (AMPK). Similar results were observed in C2C12 myoblasts treated with TNF-α and paeoniflorin. Notably, these beneficial effects of paeoniflorin on muscle atrophy were abolished by inhibiting AMPK and SIRT1 and knocking down PGC-1α. Taken together, this study showed for the first time that paeoniflorin has great therapeutic potential for CKD skeletal muscle atrophy through AMPK/SIRT1/PGC-1α-mediated oxidative stress and mitochondrial dysfunction.